Analecta Miridologica: Einige nomenklatorische Berichtigungen für die paläarktische Fauna (Hemiptera: Heteroptera). - Carvalho, José Candido de Melo (Beiträge zur Entomologie = Contributions to Entomology, 1955)
Nomenklatorische Handlungenhalimocnemis Becker, 1864 (Capsus), stat. n. now a valid taxonlinearis Fuessly, 1775 (Cimex), nom. praeocc. by Cimex linearis Fabricius, 1775; now Megalocerea recticornis (Geoffroy, 1787)californicus Van Duzee, 1917 (Excentricus), syn. n. of Ranzovius moerens Reuter, 1905mexicanus Van Duzee, 1917 (Excentricus), syn. n. of Ranzovius moerens Reuter, 1905scriptus Fabricius, 1803 (Lygaeus), nom. praeocc. by Lygaeus scriptus Fabricius, 1784; now Brachycoleus decolor Reuter, 1887punctipennis Reuter, 1879 (Malthacosoma), syn. n. of Capsus halimocnemis Becker, 1864Excentricorus Carvalho, 1955 (Miridae), gen. n.Platytomatocoris Reuter, 1883 (Miridae), syn. n. of Excentricus Reuter, 1878bicolor Mulsant & Rey, 1852 (Psallus), nom. praeocc. by Capsus bicolor Le Peletier & Serville, 1825wagneri Carvalho, 1955 (Sthenarus), nom. n. pro Psallus bicolor Mulsant & Rey, 1852, nec Le Peletier & Serville, 1825